MODEL WAKAF UANG PADA PEMBIAYAAN BARANG PUBLIK DI INDONESIA - Nova Rini (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2020)
This article aims to discuss the waqf model in the country's social financial system that can be used in Indonesia, especially in financing public goods. The analytical method used is literature study. The analysis shows that Indonesia can use the waqf money model to finance public goods by investing money waqf through Islamic financial institutions and / or Islamic financial instruments. This model is in accordance with the model that is also offered in money waqf management in Malaysia. So that the government can reduce spending especially on financing pure and mixed public goods.